1988
DOI: 10.1007/bf03350136
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and sex steroid metabolism in massively obese man

Abstract: To evaluate the effect of weight loss and diet therapy on plasma sex hormone behavior in male obesity, 9 men with a BMI of 43.4 +/- 6.3 participated in an 8-week semistarvation program [whose energy content ranged from 320 to 500 k calorie/day (proteins 44 to 60 g and carbohydrates 54 to 81 g per day)] followed by a two-week hypocaloric (1000 k calorie/day) refeeding. In basal conditions, obese patients presented higher estrogen and lower dehydroepiandrosterone sulphate, testosterone (total and free) and sex-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…We found that high fat diet resulted in significant depletion of testosterone in males, but not significant loss of estrogens in females. Obesity-induced hypogonadism has been previously described in rats [35] and humans [36], [37], and evidence suggests that the loss of testosterone in males may in turn accelerate obesity and metabolic dysfunction [38][41]. In fact, clinical studies have found that testosterone therapy can reduce features of metabolic syndrome [42][45].…”
Section: Discussionmentioning
confidence: 96%
“…We found that high fat diet resulted in significant depletion of testosterone in males, but not significant loss of estrogens in females. Obesity-induced hypogonadism has been previously described in rats [35] and humans [36], [37], and evidence suggests that the loss of testosterone in males may in turn accelerate obesity and metabolic dysfunction [38][41]. In fact, clinical studies have found that testosterone therapy can reduce features of metabolic syndrome [42][45].…”
Section: Discussionmentioning
confidence: 96%
“…Few randomized clinical studies have specifically evaluated the impact of diet and physical activity on testosterone levels in obese men. The results of these studies are essentially conflicting: some of them showed an increase of testosterone (26,27,28,29,30,31,32,33,34), others showed no change (35,36,37,38,39), and one small study has shown even a decrease in testosterone levels (40). Similarly, in the last 10 years, several trials have evaluated the impact of bariatric surgery on testosterone levels in men generally, showing an increase in testosterone levels (41,42,43,44,45,46,47,48).…”
Section: Introductionmentioning
confidence: 99%
“…(6,8) Indeed, the risk of hypogonadism in obese men is approximately twofold higher than in normal weight individuals (9). The link between excess weight and low testosterone levels is also strengthened by the reversal of sex hormone abnormalities after weight loss (10). No study has yet evaluated whether hypoandrogenism contributes to QT interval prolongation among male obese patients, indeed, no specific cause for prolonged QT interval in obese subjects has yet been identified (3,11,12).…”
Section: Introductionmentioning
confidence: 99%